Pym, A., & Assis Rosa, A. (Eds.). New directions in translation studies/Novos rumos nos estudos da tradução. Special Issue of Anglo Saxonica 3.3. - Alves, Fabio (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
Pym, A., & Assis Rosa, A. (Eds.) (2012). New directions in translation studies/Novos rumos nos estudos da tradução. Special Issue of Anglo Saxonica 3.3. Lisbon: University of Lisbon Centre for English Studies. 394p.